Inhibited autonomy for promoting physical health: qualitative analysis of narratives from persons living with severe mental illness. Issue 1 (January 2019) - Nakanishi, Miharu; Tanaka, Shintaro; Kurokawa, George; Ando, Shuntaro; Yamasaki, Syudo; Fukuda, Masato; Takahashi, Kiyohisa; Kojima, Takuya; Nishida, Atsushi
Abstract : Background: Autonomy is a key factor in the reduction of inequitable physical healthcare among people with severe mental illness compared with the general population. Aims: To clarify the critical mechanism underlying autonomy in physical health promotion based on the perspectives of people with severe mental illness. Method: We employed a conventional content analysis of narrative data from the Healthy Active Lives in Japan (HeAL Japan) workshop meetings. Results: 'Inhibited autonomy' was extracted as a central component and shaped by the users' experiences, both in a healthcare setting and in real life. This component emerged based on the lack of an empowerment mechanism in psychiatric services. Conclusions: A barrier to the encouragement of autonomy in physical health promotion was found in current psychiatric services. An effective strategy should be explored to foster an empowerment mechanism in psychiatric and mental health services. Declaration of interest: None.